MiR-203 is an independent molecular predictor of prognosis and treatment outcome in ovarian cancer: a multi-institutional study. (5th October 2019) - Panoutsopoulou, Konstantina; Avgeris, Margaritis; Mavridis, Konstantinos; Dreyer, Tobias; Dorn, Julia; Obermayr, Eva; Reinthaller, Alexander; Michaelidou, Kleita; Mahner, Sven; Vergote, Ignace; Vanderstichele, Adriaan; Braicu, Ioana; et al.
Abstract : miR-203 overexpression in ovarian tumors is associated with disease progression and worse patient's survival, independently of FIGO stage, grade, residual tumor, chemotherapy response and age. Interestingly, miR-203-incorporating multivariate models benefit disease prognosis and clinical management. Abstract: Ovarian cancer (OC) accounts for the most gynecological cancer-related deaths in developed countries. Unfortunately, the lack of both evident early symptoms and effective asymptomatic population screening results in late diagnosis and inevitably poor prognosis. Hence, it is urgent to identify novel molecular markers to support personalized prognosis. In the present study, we have analyzed the clinical significance of miR-203 in OC using two institutionally independent cohorts. miR-203 levels were quantified in a screening ( n = 125) and a validation cohort ( n = 100, OVCAD multicenter study). Survival analysis was performed using progression and death as clinical endpoint events. Internal validation was conducted by bootstrap analysis, and decision curve analysis was used to evaluate the clinical benefit. Increased miR-203 levels in OC patients were correlated with unfavorable prognosis and higher risk for disease progression, independently of FIGO stage, tumor grade, residual tumor after surgery, chemotherapy response and age. The analysis of the institutionally independent validation cohort (OVCAD study) clearly confirmed the shorter survival outcome of the patients overexpressing miR-203. Additionally, integration of miR-203 levels with the established disease prognostic markers led to a superior stratification of OC patients that can ameliorate prognosis and benefit patient clinical management. In this regard, miR-203 expression constitutes a novel independent molecular marker to improve patients' prognosis in OC.